2020
DOI: 10.1111/ijcp.13883
|View full text |Cite
|
Sign up to set email alerts
|

Lung deposition and systemic bioavailability of dose delivered to smoker compared with non‐smoker COPD subjects

Abstract: Introduction Inhaled drugs are the most commonly used class of medications for COPD subjects. No studies have been performed to assess the influence of smoking on lung deposition of aerosolized medication, especially for the exacerbated COPD subject. The present study aimed to assess the influence of smoking on the lung deposition of the aerosol delivered to exacerbated COPD subjects. Methods Twenty‐four exacerbated COPD subjects using automatic continuous positive airway pressure (Auto‐CPAP), 12 smokers (six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…This study also showed a relationship between tiotropium and CHD in the never-smoker COPD group. Although the mechanism is not clear, one study found that inhaler lung deposition was higher in non-smokers than in smokers 35 , 36 . This high lung deposition is also likely to increase the positive effect of treatment, but also leads to increased adverse effects of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed a relationship between tiotropium and CHD in the never-smoker COPD group. Although the mechanism is not clear, one study found that inhaler lung deposition was higher in non-smokers than in smokers 35 , 36 . This high lung deposition is also likely to increase the positive effect of treatment, but also leads to increased adverse effects of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%